First insights into the genetic composition of M. tuberculosis population circulating in Kosovo - Alina Minias; Magdalena Kuzioła; Florin Ahmeti; Nazmi Mehmeti; Blendi Jerliu; Greta Lila; Albuena Miftari; Xhevat Shkodra; Xhevat Jakupi; Zana Kacaniku; Monika Kozińska; Anna Zabost; et al. (Journal of Clinical Tuberculosis and Other Mycobacterial Diseases)
Tuberculosis incidence in Kosovo is among one of the highest in Europe at 33/100,000 citizens. While World Health Organization encourages epidemiological monitoring of tuberculosis transmission, studies regarding M. tuberculosis population structure in the Balkan region are limited. Here, we used spoligotyping and whole genome sequencing to describe the variation of M. tuberculosis strains circulating in Kosovo. We used samples isolated from patients in the period 2021/2022. We found that the vast majority of isolated strains belonged to spoligotype based Euro-American lineage, five strains belonged to East-Asian lineage, and one was M. caprae. We described the general characteristics of the M. tuberculosis population in our study and identified chains of transmission based on whole genome sequencing data of selected samples. Our data will be a reference point for subsequent studies of M. tuberculosis population in Kosovo.